The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00464-008-0083-x
|View full text |Cite
|
Sign up to set email alerts
|

Additional mechanical pleurodesis after thoracoscopic wedge resection and covering procedure for primary spontaneous pneumothorax

Abstract: Background Additional mechanical pleurodesis for the treatment of primary spontaneous pneumothorax (PSP) is believed to reduce the recurrence of PSP, and a covering procedure with absorbable mesh also shows comparable results. This study was conducted to determine whether additional mechanical pleurodesis would be effective in reducing recurrence after thoracoscopic wedge resection and covering procedure. Materials and methods Between May 2003 and August 2005, 99 patients underwent thoracoscopic bullectomy wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
(18 reference statements)
0
17
1
Order By: Relevance
“…These procedures can be broadly classifi ed into those targeting the site of the bullectomy and those targeting the parietal pleura. The additional procedures targeting the site of bullectomy include the application of fl eece-coated glue, 6 the attachment of an absorbent sheet, 13,16 and the spraying of a fi brin glue solution. 6 On the other hand, the additional procedures targeting the parietal pleura include mechanical abrasion of the parietal pleura, 18,21 excision of the pleura corresponding to the pulmonary apical portion, 1,8 chemical pleural adhesions using minomycin 12 and talc, 17 and further ablation of the parietal pleura using a laser 14 or argon beam.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These procedures can be broadly classifi ed into those targeting the site of the bullectomy and those targeting the parietal pleura. The additional procedures targeting the site of bullectomy include the application of fl eece-coated glue, 6 the attachment of an absorbent sheet, 13,16 and the spraying of a fi brin glue solution. 6 On the other hand, the additional procedures targeting the parietal pleura include mechanical abrasion of the parietal pleura, 18,21 excision of the pleura corresponding to the pulmonary apical portion, 1,8 chemical pleural adhesions using minomycin 12 and talc, 17 and further ablation of the parietal pleura using a laser 14 or argon beam.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,11,16 The major causal factor of this high recurrence rate is new bulla formation which, according to many reports, occurs mainly near the staple lines. 6,13,16 Therefore, it is now suggested that additional surgical procedures and remedial measures, other than bullectomy with a stapler, are necessary to ensure a low recurrence rate.…”
Section: Sp Recurrence After Stapled Bullectomy Only and Causal Factorsmentioning
confidence: 99%
See 3 more Smart Citations